Comparing the use of technology-based vs traditional team building interventions in developing group problem-solving and learning behaviours: insights from two experimental studies - Sellier, Matthew (School of Management Studies, 2022)
The increasing reliance on technology for communication seems to have shown that nontechnology or traditional team building activities may not be effective in improving certain interpersonal skills (Klein et al., 2009). The researcher investigated whether the use of a serious game, i.e. an educational video game, is a better mode of delivery to improve group problem solving, team cohesiveness, team learning behaviours and, perceived team psychological safety rather than traditional team building intervention, i.e. a non-technology-based team building intervention (Emsley & Rumeser, 2018; Edmondson, 1999). The researcher conducted two post test only quasi-experiments to compare the methods of team-building. In Study 1, four teams of university students (n=15 total students) took part in either a serious game or a traditional team building intervention. The serious game was based on a scavenger hunt mobile application while the traditional team building activity was an obstacle course. Each team was assessed, after the team building interventions, on their group problem-solving skills and team cohesiveness in order to determine if there was a significant difference between the scores of the two dimensions above for intervention groups. Study 2 consisted of six teams of university students (n=30 total students) participated in either a traditional online team-building activity or an online team-based serious game. The traditional online team-building activity was a spectrum mapping activity, and the online team-based serious game was an online escape room. Each team then participated in the same thought experiment and were finally asked to answer a questionnaire. Furthermore, a field researcher participated in both activities and her experiences were noted through an interview. There did not seem to be sufficient evidence to support the hypotheses for the second quasi experiment. However, the was evidence collected throughout both quasi-experiments that suggests that serious games are more enjoyed by participants and there seems to be a clearer initiative to utilise the interpersonal skills acquired in the future.